Inclusion of Dried or Wet Distillers' Grains at Different Levels in Diets of Feedlot Cattle Affects Fecal Shedding of Escherichia coli O157:H7 - Jacob, M. E.; Paddock, Z. D.; Renter, David G.; Lechtenberg, K. F.; Nagaraja, T. G. (My University, 2010)
Our objectives were to evaluate the prevalence of Escherichia coli O157:H7 in cattle fed diets supplemented with 20 or 40% dried distillers' grains (DG) (DDG) or wet DG (WDG) and assess whether removing DG from diets before slaughter affected fecal shedding of E. coli O157:H7. Eight hundred forty steers were allocated to 70 pens (12 steers/pen). Treatments were no DG (control), 20% DDG or WDG, and 40% DDG or WDG, and each was replicated in 14 pens. In phase 1, eight floor fecal samples were collected from each pen every 2 weeks for 12 weeks for isolation of E. coli O157:H7 and detection of high shedders. In phase 2, half of the pens with DG were transitioned to the no-DG control diet, and pen floor fecal samples were collected weekly from all pens for 4 weeks. During phase 1, prevalence of E. coli O157:H7 was 20.8% and 3.2% for high shedders. The form of DG had no significant effect on fecal E. coli O157:H7 shedding. The prevalence levels of E. coli O157:H7 and the numbers of high shedders were not different between diets with 0 or 20% DG; however, cattle fed 40% DG had a higher prevalence and more high shedders than cattle fed 0 or 20% DG (P ≤ 0.05). During phase 2, overall and high-shedder prevalence estimates were 3.3% and <0.1%, respectively, and there were no differences between those for different DG forms and inclusion levels or when DG was removed from diets. The form of DG had no impact on E. coli O157:H7; however, fecal shedding was associated with the DG inclusion level.